2012
DOI: 10.4040/jkan.2012.42.6.791
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Normal Saline for Maintenance of Arterial Lines of Surgical Patients

Abstract: Purpose: The purpose of this study was to analyze the effectiveness of saline solution vs. heparinized-saline for maintenance of arterial lines and to detect changes in platelet and aPTT as physiological indexes. Methods: In this nonequivalent control group, non-synchronized, double-blind study the effects of heparinized and saline solution on the maintenance of arterial lines were compared. Fifty five patients received the heparinized solution and fifty nine patients received the saline solution. All patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Studies on the effectiveness of flushing have indicated that it can prolong patency and prevent occlusion but will be problematic for patients with restricted fluid such as renal failure or oedema Developed a two-dimensional chart using database Micromedex, handbook of injectable drugs and stability Systematic review-no evaluation of the impact (Hanifah 2016). However, studies on the effectiveness of flushing were mostly limited on comparing heparin and normal saline (NS) (Han et al, 2012;Kumar et al, 2013)(Table II). Only one study has examined the effectiveness of bolus flushing before and after IV drug administration that reduces incompatibility incidents (Bertsche et al, 2010).…”
Section: Flushing the Medication Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on the effectiveness of flushing have indicated that it can prolong patency and prevent occlusion but will be problematic for patients with restricted fluid such as renal failure or oedema Developed a two-dimensional chart using database Micromedex, handbook of injectable drugs and stability Systematic review-no evaluation of the impact (Hanifah 2016). However, studies on the effectiveness of flushing were mostly limited on comparing heparin and normal saline (NS) (Han et al, 2012;Kumar et al, 2013)(Table II). Only one study has examined the effectiveness of bolus flushing before and after IV drug administration that reduces incompatibility incidents (Bertsche et al, 2010).…”
Section: Flushing the Medication Solutionmentioning
confidence: 99%
“…Conflicting findings on regimens have been reported. One scholar stated that NS is superior (Sotnikova et al, 2020), some scholars have reported that saline is as effective as heparin particularly for maintaining patency (Ali et al, 2015;Dal Molin et al, 2015;Gunes et al, 2018;Han et al, 2012;Sharma et al, 2019), but others have stated that heparin may prolong longer patency of IV lines (Tully et al, 2014;You et al, 2017). In response to this dispute, the first opinion presented here likely has stronger evidence and a more rigorous study conducted through randomisation and a double-blind approach (Ali et al, 2015).…”
Section: Flushing the Medication Solutionmentioning
confidence: 99%
“…In the group that was given flushing heparin with normal saline, the interventions carried out in each study were different, especially regarding the ratio of heparin and normal saline doses, which was 1:1 (Goh et al, 2011;Xiong et al, 2019) 2:1 (Han et al, 2012;Ishii et al, 2021), 6:1 (Tamura et al, 2021), and 10:1 (Alizadehasl et al, 2015;Ziyaeifard et al, 2015). In terms of research outcomes, five articles discussed the duration of arterial line patency.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…In terms of research outcomes, five articles discussed the duration of arterial line patency. The duration of the patent was determined by the time from the patient was inserted until it was removed because the arterial line was no longer needed or there was a blockage (clotting) of the catheter (Alizadehasl et al, 2015;Han et al, 2012;Ishii et al, 2021;Tamura et al, 2021;Xiong et al, 2019). In addition, three articles discuss the quality of the arterial waves generated by transducers on monitors.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation